Analisis Kesalahan Berbahasa Dan Struktur Dalam Jurnal Matematika - Ika Febriana; Nia Devi Friskauly; Cecilia Br. Perangin Angin; Sikap Ruth Br. Tumorang (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
It is very common to find journal publications and scienntific articles according to certain fields and the influence of a method on cases that have been investigated first, then reviewed in a scientific article. However, language errors are often found in scientific articles that have been read, both in spelling, punctuation, and so on. This research is qualitative research that uses descriptive methods. The data collection technique used in this research is document study. After conducting a review, the researcher still found several errors in language, for example the author still could not differentiate between standard and non-standart words. There are still structural errors. Therefore, through review by other researchers to analyze journals that have been released, it will certainly help to improve future journals.